Nanowire Electronics - Shen, Guozhen; Chueh, Yu-Lun (Nanostructure Science and Technology,, 2019)
This book gives a comprehensive overview of recent advances in developing nanowires for building various kinds of electronic devices. Specifically the applications of nanowires in detectors, sensors, circuits, energy storage and conversion, etc., are reviewed in detail by the experts in this field. Growth methods of different kinds of nanowires are also covered when discussing the electronic applications. Through discussing these cutting edge researches, the future directions of nanowire electronics are identified.